A Comparative study: Cooperative Learning in Science Learning - Zurweni Zurweni; Dwi Agus Kurniawan; Elza Triani (Jurnal Pendidikan dan Pengajaran, 2022)
A suitable learning model is needed in learning science at the junior high school level. Educators need to be able to determine the appropriate learning model for learning activities. Therefore, this study aims to analyze student responses to jigsaw and STAD learning models in SMPN and MTsN and to compare student responses to jigsaw and STAD learning models in science subjects at SMPN and MTsN. This type of research is quasi-experimental quantitative research by comparing 8 classes that use the jigsaw and STAD models in science learning. This research was carried out in 4 schools, namely 2 SMP and 2 MTs with the number of students in each class of 35 students, the number of students being 280 students. In data analysis using SPSS 26. Based on the results of the T-test, namely the value of sig. (2-tailed <0.05) it can be said that there are differences in student responses to the Jigsaw and STAD learning models in science subjects in SMP/MTs.